2020
DOI: 10.3390/coatings10050483
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Deposition and Characterization of Functional Coatings Based on an Antibacterial Gallium (III)-Chitosan Complex

Abstract: Despite their broad biomedical applications in orthopedics and dentistry, metallic implants are still associated with failures due to their lack of surface biofunctionality, leading to prosthesis-related microbial infections. In order to address this issue, the current study focuses on the fabrication and characterization of a novel type of antibacterial coating based on gallium (III)-chitosan (Ga (III)-CS) complex layers deposited on metallic substrates via electrophoretic deposition (EPD). Aiming for the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 77 publications
(82 reference statements)
4
19
0
Order By: Relevance
“…The cells are well spread on the surface of the well plate even in the high concentration of Ga (III) ions, i.e., the 1:1 Ga (III)-CS complex. The same behavior was observed in a previous study of Ga(III)-CS complex coatings, in which cells were placed in direct contact with the complexes [ 27 ]. From these observations, we can conclude that the studied concentrations of Ga (III) ions in Ga (III)-CS complexes do not lead to any adverse reactions in MG-63 cells.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The cells are well spread on the surface of the well plate even in the high concentration of Ga (III) ions, i.e., the 1:1 Ga (III)-CS complex. The same behavior was observed in a previous study of Ga(III)-CS complex coatings, in which cells were placed in direct contact with the complexes [ 27 ]. From these observations, we can conclude that the studied concentrations of Ga (III) ions in Ga (III)-CS complexes do not lead to any adverse reactions in MG-63 cells.…”
Section: Resultssupporting
confidence: 83%
“…This behavior makes Ga a suitable candidate for complexation with CS through bonding with N and O atoms from the amino and hydroxyl groups on the polymer chain and at least one water molecule, probably forming penta- or hexacoordinative complexes similar to Fe 3+ [ 11 , 24 , 25 ]. Previous works have emphasized the application of gallium-chitosan complexes for intertumoral radiotherapy [ 26 ] or orthopedic implant coatings [ 27 ]. Nevertheless, no systematic studies on the synthesis approach, as well as the structural, physical, and biological characterization of the raw complex material have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the excellent synergistic antibacterial effects of traditional antibiotics and gallium ions, combined antibacterial treatments with gallium and non-antibiotic antibacterial agents has also been explored. Akhtar et al (2020) prepared a galliumchitosan complex and performed in vitro experiments that showed that the antibacterial rate of the complex against E. coli was above 90% compared with that of single chitosan. Qiao et al (2021b) developed a triple combination strategy, as follows: 1) cationic guanidine moieties and short alkyl quaternary ammonium salts were chosen to destroy the bacterial membrane, 2) deferoxamine (DFO)-gallium conjugated to the above copolymer (namely the pGQ-DG complex) was used to disrupt iron metabolism, and 3) vancomycin (VAN) was finally added.…”
Section: Synergistic Antimicrobial Effects Between Gallium and Other ...mentioning
confidence: 99%
“…Ga 3+ ions have been also homogeneously embedded in chitosan via an in-situ precipitation method utilizing the chelation ability of chitosan [ 154 , 155 ]. The complex was then coated on a stainless-steel substrate by electrophoretic deposition (EPD).…”
Section: Gallium In Coatingsmentioning
confidence: 99%